Sri Lanka : Recent Economic Developments. (IMF Staff Country Reports; Country Report ;, 1998)
This paper reviews economic developments in Sri Lanka during 1996-98. After slowing to 4 percent in 1996, economic growth recovered to 6 1\2 percent in 1997. The slowdown in 1996 had been mainly owing to a severe drought that affected the agricultural sector and disrupted the power supply. The recovery in 1997 was strongest in agriculture and manufacturing, supplemented by continued good performance in the services sector, including a rebound in tourism. In addition, significant accomplishments were achieved in economic restructuring, including several successful privatizations and an initial step toward fiscal adjustment.